2019
DOI: 10.32736/sisfokom.v8i1.613
|View full text |Cite
|
Sign up to set email alerts
|

Desain Sistem Informasi Administrasi Bimbingan Konseling Pada Sma Negeri 1 Tempilang Dengan Model Fast

Abstract: Pendidikan di sekolah merupakan suatu hal yang sangat penting di era sekarang ini, pendidikan  merupakan akar dari peradaban suatu bangsa yang bisa mendidik serta menciptakan benih-benih penerus bangsa yang berkualitas. Pendidikan merupakan suatu kebutuhan pokok setiap orang  agar bisa menjawab tantangan kehidupan kedepan, dukungan teknologi informasi di dunia pendidikan untuk saat ini sudah banyak digunakan untuk membantu dalam hal pengurusan berkaitan dengan administrasi. Untuk saat ini, untuk proses adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
1
0
6
Order By: Relevance
“…Anisah in a study entitled Design of Counseling Guidance Administration Information System at SMA Negeri 1 Tempilang with the FAST Model concluded that a computerized information system can assist the counseling department in managing data related to counseling guidance administration so that when you want to make a counseling report, you can quickly make it, and all information related to counseling guidance can be obtained quickly and easily as needed. (Anisah Anisah, 2019) Ariani, et al, in a study entitled Designing a Web-Based Library Information System with the Framework For The Application Of System Thinking (FAST) Method concluded that the library information system website makes it easier for students to borrow books, students can find out what books are available in the library, makes it easier for admins or library staff to manage library data, such as book data, member data, borrowing and returning books, and provides an easy service process for its users. (Fattya Ariani, 2019) Misriati, et al, in a study entitled Employee Data Processing Using the FAST Method at PT Asia Berjaya Mobilindo concluded that the employee data processing system using a website with the FAST method and UML can improve services to employees in applying for leave, payroll and attendance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anisah in a study entitled Design of Counseling Guidance Administration Information System at SMA Negeri 1 Tempilang with the FAST Model concluded that a computerized information system can assist the counseling department in managing data related to counseling guidance administration so that when you want to make a counseling report, you can quickly make it, and all information related to counseling guidance can be obtained quickly and easily as needed. (Anisah Anisah, 2019) Ariani, et al, in a study entitled Designing a Web-Based Library Information System with the Framework For The Application Of System Thinking (FAST) Method concluded that the library information system website makes it easier for students to borrow books, students can find out what books are available in the library, makes it easier for admins or library staff to manage library data, such as book data, member data, borrowing and returning books, and provides an easy service process for its users. (Fattya Ariani, 2019) Misriati, et al, in a study entitled Employee Data Processing Using the FAST Method at PT Asia Berjaya Mobilindo concluded that the employee data processing system using a website with the FAST method and UML can improve services to employees in applying for leave, payroll and attendance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian tentang perancangan sistem layanan bimbingan dan konseling menggunakan metode Simple Multi Attribute Rating Technique yang digunakan untuk menentukan penanganan pelanggaran siswa [10]. Penelitian tentang perancangan sistem layanan BK dengan menerapkan metode Framework For The Application Of System Thinking (FAST) [11]. Dari penelitian tersebut di atas dihasilkan sistem informasi layanan bimbingan dan konseling berbasis web dengan fokus kepada pelanggaran siswa, tetapi belum ada yang menggunakan ruang konsultasi sebagai ruang interaksi guru dan siswa.…”
Section: Jurnal Sistem Informasi Dan Telematika (Telekomunikasi Multi...unclassified
“…Akan tetapi, walaupun konseli dapat berkomunikasi langsung dengan konselor, fakta di lapangan menunjukkan bahwa tidak semua aktivitas konseling berlangsung dengan baik. Tidak semua orang dapat melakukan konsultasi secara langsung dengan konselor (Anisah, 2019). Ada beberapa konseli yang belum dapat melakukan konseling dengan konselor secara efektif di sekolah atau di kampus.…”
Section: Pendahuluanunclassified